Microstrip Cross-coupled Interdigital SIR Based Bandpass Filter - Maharjan, Ram Krishna; Shrestha, Bhanu; Kim, Nam-Young (Společnost pro radioelektronické inženýrství, 2012)
A simple and compact 4.9 GHz bandpass filter for C-band applications is proposed. This paper presents a novel microstrip cross-coupled interdigital half-wavelength stepped impedance resonator (SIR) based bandpass filter (BPF).The designed structure is similar to that of a combination of two parallel interdigital capacitors. The scattering parameters of the structure are measured using vector network analyzer (VNA). The self generated capacitive and inductive reactances within the interdigital resonators exhibited in a resonance frequency of 4.9 GHz. The resonant frequency and bandwidth of the capacitive cross-coupled resonator is directly optimized from the physical arrangement of the resonators. The measured insertion loss (S21) and return loss (S11) were 0.3 dB and 28 dB, respectively, at resonance frequency which were almost close to the simulation results.
Keywords: Bandpass filter; interdigital resonator; stepped impedance resonator (SIR); half wavelength SIR resonator